Indian indenture: History and historiography in a nutshell. Issue 1 (1st September 2021) - Lal, Brij V.
Abstract : The establishment of the academic study of Indentureship is a relatively recent development that has been led by descendants of indentured labourers from across the diaspora. This article highlights key moments in both the history and historiography of Indentureship. Looking first at the system established by the British on plantations across their colonies, it goes on to consider the variety of labourers' backgrounds and the process of social equalisation that was fostered by both voyage and plantation. Considering the injustices of the system, the author emphasises the ways in which labourers were able to disrupt the power of the plantocracy and analyses the particular perils the system held for women. The religious life of the labourers as well as the maintenance of the Panchayat and the importance of the Ramayana are also weighed. The historiography section of this article traces the attention paid to the system of indenture and the diaspora it created; from the initial attentions of missionaries and 'benevolent' organisations in the nineteenth century to the creation of a global network of scholars of Indentureship with roots in South Africa, Fiji, Mauritius, Guyana and Trinidad. It further emphasises key moments and publications during this period.